USING AUTHENTIC MATERIALS TO IMPROVE LISTENING COMPREHENSION IN ESL CLASSROOMS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
Listening comprehension is a key aspect of language acquisition for English as a Second Language (ESL) learners. Traditional classroom audio often lacks the variety and realism of everyday language, which can hinder students' ability to understand natural spoken English. This study investigates the use of authentic materials (e.g., news clips, podcasts, interviews, movies) in improving listening comprehension among intermediate ESL learners. Findings from a four-week intervention show that students exposed to authentic listening sources demonstrated higher comprehension levels, increased motivation, and better retention compared to those using textbook-only audio.